An unconditional basic income in the family context: Labor supply and distributional effects - Julia Horstschräer; Markus Clauss; Reinhold Schnabel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
In this paper we estimate the effects of an unconditional basic income on labor supply and income distribution with a special focus on the incentives to work in the family context. An unconditional basic income guarantees every citizen a minimum income without any means-testing. We simulate a proposed basic income reform with a detailed microsimulation model, estimate labor supply reactions with a structural labor supply model and perform distributional analysis using micro data from the German Socio-Economic Panel. As the originally proposed basic income concept yields a very high deficit, we also analyze two budget neutral alternatives. Comparing labor supply and distributional results of the budget neutral alternatives, the well-known equity-effciency trade-off is unveiled. In the family context our analyzes suggest that the unconditional character of the basic income causes increasing family incomes, but also serious disincentives to work for secondary earners.
Keywords: C15; D31; D78; H31; H53; J08; J22; 330; basic income; negative income tax; flat tax; female labor supply; Soziale Mindestsicherung; Wirkungsanalyse; Arbeitsangebot; Familienökonomik; Verteilungswirkung; Negative Einkommensteuer; Flat Tax; Steuerwirkung; Mikrosimulation; Deutschland